Immobilization of Chlorella vulgaris for Palm Oil Mill Effluent(POME) Treatment and Heavy Metals Removal - Nazily, Siti Ameera Nadya (IRC, 2016)
Being one of the major aquatic pollutants in Malaysia, palm oil mill effluent or POME contains harmful organic soluble materials, specifically nitrogen and organic carbon. Not only that, POME also has a high level of chemical oxygen demand (COD), biological oxygen demand (BOD) and heavy metals content which can critically jeopardize the environment by causing eutrophication. Hence, POME must be discharged to the environment as treated wastewater with the nutrients efficiently removed. Treatment of wastewater with the usage of immobilized microalgae has been proved to have significant advantages over the conventional treatment. Therefore, in this project, Chlorella vulgaris is specifically chosen as the focused species of microalgae where it is cultured, immobilized in alginate beads and undergoes nutrient removal experiments.